United States State-Level Variation in the Use of Neuraxial Analgesia During Labor for Pregnant Women. Issue 3 (September 2019) - Butwick, A.J.; Bentley, J.; Wong, C.A.; Snowden, J.M.; Sun, E.; Guo, N.
Abstract : ( JAMA Netw Open . 2018;1:e186567) Guidelines for levels of maternal care for obstetric analgesia and anesthesia, as per the American College of Obstetricians and Gynecologists, state that anesthesia services should be available in all hospitals offering maternal care. However, there is insufficient research to determine the extent or characteristics of the geographic variability across US states in neuraxial analgesia use. The authors of the present study used multilevel modeling, accounting for patient-level and state-level factors, to assess variability in neuraxial analgesia practices in the United States in 2015.